ZnO@ZIF-8 Nanoparticles as Nanocarrier of Ciprofloxacin for Antimicrobial Activity - Bruno Altran Costa; Marina Paiva Abuçafy; Thúlio Wliandon Lemos Barbosa; Bruna Lallo da Silva; Rafael Bianchini Fulindi; Guilherme Isquibola; Paulo Inácio da Costa; Leila Aparecida Chiavacci (MDPI AG, 2023)
Numerous antimicrobial drugs have been prescribed to kill or inhibit the growth of microbes such as bacteria, fungi, and viruses. Despite the known therapeutic efficacy of these drugs, inefficient delivery could result in an inadequate therapeutic index and several side effects. In order to overcome this adversity, the present study investigated antibiotic drug loading in zeolitic imidazolate frameworks (ZIFs), in association with ZnO nanoparticles with known antimicrobial properties. In an economic synthesis method, the ZnO surface was first converted to ZIF-8 with 2-methylimidazole as a ligand, resulting in a ZnO@ZIF-8 structure. This system enables the high drug-loading efficiency (46%) of an antimicrobial drug, ciprofloxacin, within the pores of the ZIF-8. This association provides a control of the release of the active moieties, in simulated body-fluid conditions, with a maximum of 67% released in 96 h. The antibacterial activities of ZnO@ZIF-8 and CIP-ZnO@ZIF-8 were tested against the Gram-positive Staphylococcus aureus strain and the Gram-negative Pseudomonas aeruginosa strain, showing good growth inhibition. This result was obtained by combining ZnO@ZIF-8 with ciprofloxacin in a minimal inhibitory concentration (MIC) that was 10 times lower than ZnO@ZIF-8 for S. aureus and 200 times lower for P. aeruginosa, suggesting that CIP-ZnO@ZIF-8 may have potential application in prolonged antimicrobial treatment.